Editorial: the impact of red blood cell transfusion on inpatient mortality in upper gastrointestinal bleeding—authors' reply. Issue 2 (24th June 2022) - Radadiya, Dhruvil; Devani, Kalpit; Rockey, Don C.
LINKED CONTENT: This article is linked to Radadiya et al papers. To view these articles, visit https://doi.org/10.1111/apt.16965 and https://doi.org/10.1111/apt.17048